Dietary fatty acids and risk of non-alcoholic steatohepatitis: A national study in the United States - Lu, Xiao-Ting; Wang, Yong-Dong; Zhu, Ting-Ting; Zhu, Hui-Lian; Liu, Zhao-Yan (Frontiers in Nutrition, 2022)
Background: Nonalcoholic steatohepatitis (NASH), the early invertible stage of nonalcoholic fatty liver disease, has become a public health challenge due to the great burden and lack of effective treatment. Dietary nutrients are one of the modifiable factors to prevent and slow down disease progression. However, evidence linking dietary fatty acids intake and risk of NASH is lacking. Objectives: This study aimed to examine the association between dietary total saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs), their subtypes, the ratio of unsaturated (UFAs) to SFAs, and the risk of NASH among a nationwide population in the United States. Methods: This cross-sectional study was conducted among 4161 adults in the National Health and Nutrition Examination Survey in 2017–2018 cycle. NASH was defined by transient elastography. Dietary fatty acids were assessed using a validated 24-hour food recall method. Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (95%CIs). Results: A total of 2089 (50.2%) participants with NASH were identified. Compared with participants in the bottom tercile of dietary intakes of total PUFAs, those in the highest tercile had lower risk of NASH, with an adjusted OR of 0.67 (95% CI: 0.46–0.97). Similar associations were found between the subtype of PUFA 18:3 and NASH, while the fully adjusted OR in the highest tercile was 0.67 (95% CI: 0.47–0.96). Interactions of dietary PUFAs and body mass index (BMI) could be found influencing NASH risk. Stronger associations of dietary total PUFAs intakes with NASH risk were found in obese participants (OR, 95% CI: 0.41, 0.22–0.75) than in the non-obese participants (OR, 95% CI: 1.00, 0.70–1.43; P-interaction = 0.006). Similar effects on risk of NASH were also observed between BMI and dietary intakes of PUFA 18:3. However, no significant associations were observed between NASH risk and dietary total SFAs, MUFAs, their subtypes as well as the ratio of UFAs to SFAs. Conclusions: Dietary intakes of total PUFAs, as well as its subtype of PUFA 18:3, were inversely associated with risk of NASH. Further large prospective studies need to be conducted to confirm our findings.